Psychological Capital ditinjau dari Sense of Humor Karyawan pada Suatu Perusahaan yang bergerak di Bidang Distributor di Kabupaten Deli Serdang - Arfin; Winida Marpaung (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this study is to find out about the relationship between sense of humor and psychological capital. The hypothesis that the researchers propose in this study is that there is a positive and significant relationship between sense of humor and psychological capital, assuming that the higher sense of humor, the higher psychological capital and conversely. The selection of participants for this study use purposive sampling. The sample of this research is 89 employees that who are minimal 21 years old and work over 2 years on this company. The data that collected by the researchers comes from the results with a scale that has been prepared with reference from the theoretical dimensions used by the researchers to measure sense of humor and psychological capital using the SPSS 21.00 for windows. The correlation coefficient obtained was 0.902 (p<0.005). From this results, there is a positive and significant relationship between the variables, sense of humor and psychological capital. The results of this study contribute to the Industrial and Organizational Psychology sector in particular to increase psychological capital